2021
DOI: 10.3390/polym13111816
|View full text |Cite
|
Sign up to set email alerts
|

Residual Birch Wood Lignocellulose after 2-Furaldehyde Production as a Potential Feedstock for Obtaining Fiber

Abstract: From birch wood, it is possible to obtain both acetic acid and 2-furaldehyde as valuable value-added products. The main objective of this study was to develop a new wasteless technology for obtaining 2-furaldehyde, acetic acid, and lignocellulose (LC) residue usable as feedstock in further processing such as thermomechanical (TMP), alkaline peroxide mechanical (APMP), and sulfate pulping processes. To achieve this objective several screening tests were performed, and a further experimental plan was developed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Birch wood, which we studied previously, being a hardwood, has different acid-soluble lignin and acid-insoluble lignin content (19.42% and 3.71%, respectively) when compared to oat husks (2.99% and 12.99%, respectively), which can affect biomass processing efficiency, indicating the need for separate reaction parameter optimization. Glucan and xylan content in oat husks (39.17% and 23.58%) compared to birch wood chips (37.84% and 21.96%) is similar, indicating that the furfural yield after the optimization of process parameters should be similar for both types of feedstocks [ 32 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Birch wood, which we studied previously, being a hardwood, has different acid-soluble lignin and acid-insoluble lignin content (19.42% and 3.71%, respectively) when compared to oat husks (2.99% and 12.99%, respectively), which can affect biomass processing efficiency, indicating the need for separate reaction parameter optimization. Glucan and xylan content in oat husks (39.17% and 23.58%) compared to birch wood chips (37.84% and 21.96%) is similar, indicating that the furfural yield after the optimization of process parameters should be similar for both types of feedstocks [ 32 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ] showed that there are a lot of technological parameters that can affect the outcome of target biobased products. Therefore, the effect of the variables of catalyst concentration (c), temperature (T), catalyst amount (m), treatment time (τ) has been studied (see Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…An H 3 PO 4 acid solution of a varied concentration (55–85%) was used as a catalyst. After combining the chips with a certain amount of the catalyst (3 wt.%), the resulting material was treated with a continuous superheated steam flow in an original bench-scale reactor, as detailed in our earlier papers [ 15 , 16 ]. The diameter of the main reactor camera was 110 mm, its height was 1450 mm, its volume was 13.7 L, and its max pressure was 1.2 MPa [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Characterization of the chemical composition was carried out at the Latvian State Institute of Wood Chemistry as reported elsewhere [11].…”
Section: Chemical Compositionmentioning
confidence: 99%